2018
DOI: 10.18632/oncotarget.25100
|View full text |Cite
|
Sign up to set email alerts
|

Four immunohistochemical assays to measure the PD-L1 expression in malignant pleural mesothelioma

Abstract: Immune checkpoint inhibitors (ICIs) targeting the PD-1/PD-L1 pathway are expected to be a novel therapy for combating future increases in numbers of malignant pleural mesothelioma (MPM) patients. However, the PD-L1 expression, which is a predictor of the response to ICIs, is unclear in MPM. We studied the PD-L1 expression using four immunohistochemical assays (SP142, SP263, 28-8 and 22C3) in 32 MPM patients. The PD-L1 expression in tumor cells and immune cells was evaluated to clarify the rate of PD-L1 express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…Our results showed that PD-L1 expression does not appear to be significantly associated with survival despite a trend toward a poorer prognosis with PD-L1 expression in ≥50% on tumor cells. The absence of a significant association with survival is in agreement with two recent studies, in which a specific antibody (SP142) (38) and four different antibodies were employed (17). This finding was observed even when we compared survival with PD-L1 expression on TILs, and with the combined expression of tumor cells and TILs.…”
Section: Pd-l1 ≥1% Pd-l1 <1% ----------------------------------------supporting
confidence: 92%
See 2 more Smart Citations
“…Our results showed that PD-L1 expression does not appear to be significantly associated with survival despite a trend toward a poorer prognosis with PD-L1 expression in ≥50% on tumor cells. The absence of a significant association with survival is in agreement with two recent studies, in which a specific antibody (SP142) (38) and four different antibodies were employed (17). This finding was observed even when we compared survival with PD-L1 expression on TILs, and with the combined expression of tumor cells and TILs.…”
Section: Pd-l1 ≥1% Pd-l1 <1% ----------------------------------------supporting
confidence: 92%
“…Of note, we reported an association between PD-L1 positivity and histotype. Furthermore, some studies have found lower PD-L1 expression in epithelioid subtype compared with other subtypes (15)(16)(17)(18). PD-L1 on tumor cells was not always expressed simultaneously with PD-L1 on TILs as already reported (15,16,21) and in concordance with the findings in other tumor types (33).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Quantification of PD‐L1 expression in patients with advanced NSCLC is useful for predicting the response to immunotherapy with checkpoint inhibitors that disrupt the PD‐1/PD‐L1 interaction . Two commercially available PD‐L1 IHC assays, the PD‐L1 IHC 22C3 pharmDx and the Ventana PD‐L1 SP263 assays, have been shown to be highly concordant in quantifying PD‐L1 expression regardless of the TPS cutoff levels or sample type (surgical resections/biopsies vs cytological specimens) …”
Section: Discussionmentioning
confidence: 99%
“…Data from the Cancer Genome Atlas and Foundation Medicine indicated a low tumor mutation burden in thymomas and thymic carcinomas; only 6% of carcinoma cases had >10 mutations/Mb and 3% had >20 mutations/Mb (Figure 2) [13,15]. [30] TMA, clone 5H1 (intensity high) 65 44 (68%) 4 3 (75%) Arbour et al [31] Slides, clone E1L3 (25% of tumor cells cut off) 12 11 (94%) 11 4 (34%) Yokohama et al [32,33] Slides, EPR1161 (H-score, 20% of tumor cells cut off) 82 44 (54%) 25 20 (80%) Weissferdt [34] Slides, clone E1L3 (5% of tumor cells cut off) 74 47 (64%) 26 14 (54%) Markevski et al [28] Slides, clone SP142 (1% of tumor cells cut off) 38 35 (92%) 8 4 (50%) Wei et al [35] TMA, clone E1L3 (% of cells and intensity) 100 100 (100%: 36% low, 64 high) 69 69 (100%: 64% low, 36% high) Guleria et al [36] TMA, clone SP263 (1-25% of tumor cells cut off) 84 69 (82%) Suster et al [37] TMA, clone SP142 (1-50% of tumour cells cut off) 21 (lymphoepithelioma like histology) 15 (71%: 67% high, 33% low) Tiseo et al [38] TMA, clone E1L3 (H-score, 1% of tumor cells cut off) 87 16 (20%) 25 13 (52%) Bagir et al [39] Slides, clone AM26531AF-N (intensity) 37 21 (57%) 6 4 (67%) Sakane et al [40] Slides…”
Section: Pathogenesis Of Autoimmunity In Thymic Epithelial Tumorsmentioning
confidence: 99%